(untitled) (Journal of Psychiatrists’ Association of Nepal, 2026)
Background: Bipolar disorder (BD) affects 1% of the global population, yet erectile dysfunction (ED) during euthymia remains poorly understood, particularly in Nepal, where cultural taboos suppress discussion of sexual health. This study aimed to identify clinical and socio-demographic correlates of ED among euthymic male patients with bipolar disorder. Material and methods: We conducted a cross-sectional study at Mental Hospital, Lagankhel, Nepal, recruiting 185 euthymic males of age 18-60 years through outpatients via convenience sampling. Euthymia was confirmed using Young’s Mania Rating Scale <5 and Hamilton Depression Rating Scale <8. Erectile function was assessed with the abridged IIEF-5; scores ≤21 indicated ED. Data were analyzed using SPSS v29 with descriptive statistics and Spearman’s correlation. Results: Mean age of participants was 36.48±11.42 years. ED was present in 68.1% of the participants: mild (23.8%), mild-moderate (20%), moderate (7.6%), and severe (16.8%). Significant correlates included older age (r = −0.47, < 0.001), longer illness duration (r = −0.37, p < 0.01) and married participants (p = 0.007). Residence, occupation, religion, socioeconomic status, education and substance use showed no significant correlation. Among the various medication combinations, patients on mood stabilizers plus antidepressants showed the highest ED rate (80%). Conclusion: ED is highly common in euthymic bipolar men and linked to age, illness duration, and antidepressant use. Findings support integrating routine, culturally sensitive sexual health screening into psychiatric care to improve holistic outcomes.